2011
DOI: 10.1002/cvde.201004291
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Vanadium Oxide Films with a Novel Vanadium(III) Precursor

Abstract: Vanadium forms several oxides with a wide variety of properties and technological applications in the fields of catalysis, solid-state batteries, electrochromic devices, and infrared modulators. [1][2][3][4] The ability of vanadium atoms to possess multiple oxidation states, and the facile conversion between oxides of different stoichiometry, makes the synthesis of pure vanadium oxide phases complicated. [5,6] Divanadium pentaoxide (V 2 O 5 ) and vanadium dioxide (VO 2 ) are the two main oxide phases, and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…[173,174] This crystalline phase was also observed as a dominant structure using PECVD at 207-72°C starting from VO(O i Pr) 3 under oxygen-rich conditions. [175] Crociani et al [176] have investigated V(O-C-(CH 3 ) 2 CH 2 OCH 3 ) 3 and reported the possibility of growing either VO 2 or V 2 O 5 at 550°C via a fine adjustment of the oxygen/water ratio as the reactant gas. The CVD of V 2 O 5 was reported starting from VO(OC 2 H 5 ) 3 , [177,178] and VO(OC 3 H 7 ) 3 resulting in the growth of V 2 O 5 and V 6 O 13 thin films at 350-00°C.…”
Section: Vanadium Alkoxide Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[173,174] This crystalline phase was also observed as a dominant structure using PECVD at 207-72°C starting from VO(O i Pr) 3 under oxygen-rich conditions. [175] Crociani et al [176] have investigated V(O-C-(CH 3 ) 2 CH 2 OCH 3 ) 3 and reported the possibility of growing either VO 2 or V 2 O 5 at 550°C via a fine adjustment of the oxygen/water ratio as the reactant gas. The CVD of V 2 O 5 was reported starting from VO(OC 2 H 5 ) 3 , [177,178] and VO(OC 3 H 7 ) 3 resulting in the growth of V 2 O 5 and V 6 O 13 thin films at 350-00°C.…”
Section: Vanadium Alkoxide Compoundsmentioning
confidence: 99%
“…Crociani et al have investigated V(O‐C(CH 3 ) 2 CH 2 OCH 3 ) 3 and reported the possibility of growing either VO 2 or V 2 O 5 at 550°C via a fine adjustment of the oxygen/water ratio as the reactant gas. The CVD of V 2 O 5 was reported starting from VO(OC 2 H 5 ) 3 , and VO(OC 3 H 7 ) 3 resulting in the growth of V 2 O 5 and V 6 O 13 thin films at 350–00°C …”
Section: Cvd Of Vanadium Oxidementioning
confidence: 99%
“…The growth of single phase VO 2 remains a challenge due to the fact that a number of stable phases of vanadium oxides could form in a narrow range of composition, thus, requiring a strict control on growth conditions for obtaining a single pure phase of VO 2 . Various types of thin film deposition techniques have been employed for VO 2 film synthesis like pulsed laser deposition (PLD) , molecular beam epitaxy (MBE) , magnetron sputtering , chemical vapour deposition (CVD) , sol–gel processing and atomic layer deposition . In this study, we use direct liquid injection–metal organic chemical vapour deposition (DLI–MOCVD) and a single source precursor to grow VO 2 films of varying thickness and microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Several thin lm growth techniques, such as molecular beam epitaxy, 16 sputtering, 17 pulsed laser deposition, 18 electrodeposition, chemical vapor deposition, 19 and atomic layer deposition (ALD) 4 have been used to deposit VO x thin lms with different stoichiometries. ALD is a proven, extraordinarily controllable thin lm deposition technique with great features, including atomically precise lm thicknesses due to self-limiting reactions, uniform and conformal growth over large areas as well as over three-dimensional structures, pinhole free morphologies, and high reproducibility.…”
Section: Introductionmentioning
confidence: 99%